Determining factors of attitudes and intentions towards downloading: an australian perspective - Teah, Min (School of Marketing, Curtin Business School, 2010)
Digital piracy has been a rampant phenomenon that has attracted attention both from major corporations, policy makers and the media. This study investigates the factors influencing "illegal" downloading of movies and TV series through P2P networks to gain a better understanding of downloaders. Specifically, it examines how social and ethical orientations of university students and their attitudes towards downloading impact on downloading intentions. The data analysis of 284 useable responses produced several significant relationships. Neutralisation theory and the theory of planned behavior are used to explain some of the results. Facilitating conditions and personal moral obligation were found to predict attitudes towards downloading. Personal moral obligation and attitudes towards downloading are also found to influence intentions to download. Findings derived from this study can provide useful managerial implications for marketers and policy makers to have a better understanding of down-loaders and help developed better measures to a problem which is likely to persist.